An agglomeration strategy for accelerating RBF-based mesh deformation. (May 2017) - Strofylas, Giorgos A.; Lygidakis, Georgios N.; Nikolos, Ioannis K.
Highlights: A methodology for the reduction of the RBF centers for mesh deformation is developed. It is based on the agglomeration of boundary nodes' control areas. The fusion strategy is performed on a topology-preserving framework. It considerably improves computational performance of the grid deformation procedure. It preserves geometry properties and grid quality. Abstract: RBF-based mesh deformation methods have been recognized during the past years as an essential tool for numerical simulations involving mesh deformation. Nevertheless, they call for excessive memory and computation time requirements, especially for large-scale problems. A remedy to this shortcoming appears to be the selection of a reduced number of surface mesh nodes, to be used as RBF-centers, resulting in decreased dimensions of the system of equations. In this study a methodology for the reduction of the RBF-centers is developed, based on the agglomeration of boundary nodes' control areas. This technique has been adopted from the multigrid methods frequently employed in numerical simulation of fluid flow, heat transfer, etc. The fusion strategy is performed on a topology-preserving framework, while it resembles the advancing front technique, as it begins from regions with surface discontinuities extending successively to the interior. The proposed algorithm was evaluated against benchmark test cases, concerning deformation of the wing of a transonic commercial aircraft and the blade of a wind turbine, revealing its potential for radically improved computational performance of the grid deformation procedure. Moreover, the obtained results confirm its capability to preserve grid quality, despite the notable reduction of RBF-centers.